Improving the gel properties of transgenic microbial transglutaminase cross-linked soybean-whey mixed protein by ultrasonic pretreatment. (April 2020) - Cui, Qiang; Wang, Guorong; Gao, Da; Wang, Lin; Zhang, Anqi; Wang, Xibo; Xu, Ning; Jiang, Lianzhou
Graphical abstract: Highlights: Preliminary exploration of the structure of soy and whey protein. The co-aggregation of soy and whey protein mixed systems was presented. The mechanism of the gelation of soy and whey protein mixed systems was briefed. The interfacial synergism of soy and whey protein mixed systems was discussed. Effect of ultrasonic pretreatment on mixed protein gel under the action of MTG. Abstract: This study investigated the effect of microbial transglutaminase cross-linking on the gel properties of soybean-whey mixed protein (SPI-WPI) after ultrasonic pretreatment. The average particle size of SPI-WPI decreased with increasing of ultrasonic time treatment, and minimal particle size was verified after 45 min. Endogenous fluorescence spectroscopy and surface hydrophobicity analysis showed that the SPI-WPI conformation changed after ultrasonic treatment. The polypeptide chain partially expanded inside the protein molecule, the hydrophobic group was exposed, and the protein structure became more stretched. The gel hardness and water holding capacity of the SPI-WPI hybrid system reached a maximum 30 min after ultrasonic treatment. Fourier infrared analysis showed that the secondary structure of the protein changed after ultrasonic modification. A complex is formed between SPI and WPI, and the gel properties of the mixed protein are significantly improved, providing theoretical and technical support for the development of new mixed protein foods.